PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN MINAT BELAJAR SISWA MTsN JAMBEWANGI - Lutfi, Miftakhul (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2017)
This study aims to determine the effectiveness of the mind mapping method to increase student learning interest in integrated Social Sciences subjects class VIII A MTsN Jambewangi Selopuro Blitar. The research method uses a qualitative approach, while the type of research used is qualitative and quantitative. Qualitative data, namely the influence of student learning interest during the learning process takes place using the mind mapping method. The data sources in this study were class VIII A MTsN Jambewangi which numbered 36 students. The results showed that the mind mapping method can increase the learning interest of class VIII A students of MTsN Jambewangi, proven to increase the first cycle by 72.3 while in the second cycle to 82.9 while in the third cycle it became 94.7. While the influence of interest in learning can be seen that the average value in the first cycle is 2.1, in the second cycle becomes 2.9 while in the third cycle is 3.8.Keywords: mind mapping method; ability to increase learning interest